The Strategy of the Radicalism Movement in Building a Culture of Islamophobia in Indonesia - Tonny Ilham Prayogo; Alif Nur; Arum Setyowati (Qolamuna : Jurnal Studi Islam, 2023)
Abstract: Islamophobia is an issue of thoughts and views that triggers the growth of conflicts, disputes, and intolerance in social and religious life. Along with the news about Islamophobia issues, this incident re-opened the memory of the Indonesian people from 1970-2007 about acts of terrorism based on radicalism. This is a problem in the order of people's lives, as well as an alarm for the government and society that radical ideology still exists and will become a ticking time bomb that will continue to haunt the country if it is not taken seriously. This study aims to open 'dark glasses' to understand the meaning of Radical and know the dangers of radicalism, especially if it is coupled with misunderstandings in text and context. This research is a qualitative study with descriptive analysis methods and epistemological approaches that use literature searches through various print and mass media sources. The novelty in this study are that Islamophobia is the result of contemporary ideas through the strategy of the radicalism movement. Therefore, the writer concludes that understanding the meaning of radical and radicalism can be interpreted according to who interprets it; it can be positive or negative. Second, the rejection of westernization and modernization is considered to have made most of them lose global competence, so radicalism is taken as a way to escape the bondage of Western hegemony. Keywords: Radicalism, Islamophobia, Radical, Modernization